Implementation Of The Curriculum And Teaching In Early Childhood Education In The City Of Ambon - M. Faqih Seknun (Green Publisher Indonesia, 2024)
This research focus consists of: first, how is the Early Childhood Education curriculum (PAUD)? Second How to develop the PAUD curriculum in learning activities? Third How is the implementation of learning in PAUD in Ambon City? Of the three problems can be explained below. The aim of research to found the real condition of learning in the PAUD school in Ambon, and also to know about the implementation of curriculum and learning process in Ambon This study uses qualitative and quantitative approaches with descriptive analysis, and data analysis based on statistical data, data collection using questionnaires, interviews, observation and documentation. researchers dropped directly in schools where the study was conducted by interviewing the headmaster, the teachers and get data through questionnaires and questionnaires given to 10 schools in the study location. Research results found: First, the curriculum used by PAUD schools in Ambon city is the K13 curriculum and KTSP but schools still form additional curriculum based on student conditionality. Most PAUD schools have not carried out active learning, this is because in the PAUD curriculum itself it is still not coercive. Thus, for learning such as in elementary school (SD) it has not been implemented. According to them, that PAUD students focus more on playing and in that game they will think for themselves related to knowledge. Secondly, 100% have not been implemented in PAUD schools. In implementing the curriculum in PAUD schools always formulate learning objectives that are appropriate to the conditions of each school.